Case Report: Novel compound heterozygous mutations in PNPLA6 gene associated with Oliver-McFarlane syndrome - Zheng, Jia; Wang, Zhe; Li, Keqing; Chen, Lixia; Luo, Yayin; Yu, Fei; Wang, Dan; Yu, Guangxiang (Frontiers in Genetics, 2025)
BackgroundOliver-McFarlane syndrome (OMCS) is an extremely rare congenital disorder that presents with hypogonadotropic hypogonadism, long eyelashes and eyebrows, pigmentary retinopathy, peripheral nerve axon neuropathy and other associated features. It is currently known that OMCS is linked to variants in the patatin-like phospholipase domain containing 6 (PNPLA6) gene, but the specific pathogenic mechanism is still unclear.MethodsWe performed Whole exome sequencing (WES) on the proband and his parents, followed by validation of the findings through Sanger sequencing and Reverse Transcription-Polymerase Chain Reaction (RT-PCR) analysis.ResultsSanger sequencing identified two compound heterozygous variants in the PNPLA6 (NM_006702.5) gene in the proband: c.3184G>A (p.Val1062Met) and c.2704-18C>G. According to the ACMG guidelines, the c.3184G>A variant is classified as likely pathogenic, while the c.2704-18C>G variant is discovered for the first time. Segregation analysis further revealed that the c.3184G>A variant was inherited from the father, whereas the c.2704-18C>G variant was derived from the mother—consistent with an autosomal recessive inheritance pattern. RT-PCR detected that the c.2704-18C>G variant caused a 29bp deletion upstream of exon 26, resulting in a splice site mutation (p.His902Alafs108).ConclusionWe report a case from China of PNPLA6 gene variants leading to Oliver-McFarlane syndrome, with the patient exhibiting typical characteristics of OMCS. Our findings further substantiate the pathogenicity of PNPLA6 gene variation in OMCS, broadening the established genotypic spectrum of the PNPLA6 gene. These findings enhance the understanding of its pathogenesis and offer perspectives for clinical diagnosis and management.